Phase-lagged formulation of quantum mechanics : application to ultra-fast processes of energy and information transport - Abouzar, Kaboudian (2009)
In this report, a brief history of quantum mechanics and the major attempts and developments in the early days of quantum mechanics is presented. It is addressed that the Schrodinger equation, the corner stone in quantum mechanics, gives rise to the paradox of instantaneous propagation of energy. It is underlined that the Schrodinger equation is not a relativistic formula. Major attempts to overcome the paradox and to make the formulation relativistic are addressed. It is discussed that, despite of all the attempts, no unique and general formulation which removes the paradox and gives relativistic results in all cases is ever proposed.